Vertical barangay designing a holistic public housing complex in the Metro Manila urban setting - Guerrero, Paolo Dominic N.; Ruby Teresa M. de Leon (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
In light of the current housing backlog in the Philippines, and the ongoing 4PH program which
seeks to address this backlog, there is interest in creating and implementing architectural
designs for multi-storey mid/high-rise urban housing developments. With this context, the work
sought to design a vertical social housing complex in the vicinity of NAIA terminal 1, within the
emerging Priority Development Zone of Pasay City. In creating the design, a review of studies
and precedents of social housing developments was done; supplemented by data from reports
on local housing projects, and responses from interviews with housing stakeholders. From this
research and the user and spatial analyses done, three concepts emerged for each level of the
design: Space Efficiency at the unit-level, Openness at the building-level, and the Barangay
experience at the complex-level. Three unit designs were made (Studio, 1BRLDK, 2BRDK),
each intended to suit the needs of families based on their situation. A twin building design
emerged from the design process; the design was intended to encourage interaction by opening
the space and providing communal spaces on each floor. Lastly, the complex was designed with
the intent of supporting a Barangay; amenities commonly found in Barangays (i.e. basketball
court, wet market, barangay hall) alongside communal spaces dedicated to assemblies and
collaborative activities. The design proposes a socialized housing complex that is able to cater
to the needs of the residents, provide spaces that support the community building experience,
and enable the formation and longevity of a new Barangay.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Housing -- Metro Manila; Public housing -- Metro Manila